The Vichy past in France today : corruptions of memory - Golsan, Richard Joseph, 1952- (Lexington Books, an imprint of The Rowman and Littlefield Publishing Group, Incorporated, 2017)
This study examines the continuing impact of the memory of the Vichy regime and World War II in France. It analyzes recent political and intellectual debates, trials and the passage of contentious laws, historical controversies, and literary works and argues that the country has not yet reconciled with its past.